Neutrophil‐to‐lymphocyte and platelet‐to‐lymphocyte ratio and disease activity in rheumatoid arthritis: A systematic review and meta‐analysis. (24th September 2022) - Zinellu, Angelo; Mangoni, Arduino A.
Abstract: Background: Inflammatory indexes derived from routine haematological parameters, particularly the neutrophil‐to‐lymphocyte ratio (NLR) and the platelet‐to‐lymphocyte ratio (PLR), have been shown to discriminate between patients with and without rheumatoid arthritis (RA). However, their capacity to discriminate between RA patients with and without active disease has not been systematically appraised. Methods: We searched PubMed, Web of Science, Scopus and Google Scholar, from inception to June 2022, for studies comparing NLR and/or PLR values between RA patients with and without active disease. Risk of bias and certainty of evidence were assessed using the Joanna Briggs Institute Critical Appraisal Checklist and GRADE, respectively. Results: In 18 studies (2122 RA patients with active disease, mean age 50 years, 20% males; 1071 RA patients with nonactive disease, mean age 50 years, 25% males), active disease was associated with significantly higher NLR (standard mean difference, SMD = 0.37, 95% CI 0.19 to 0.55, p  < .001; low certainty of evidence) and PLR values (SMD = 0.48, 95% CI 0.32 to 0.64, p  < .001; low certainty of evidence). In sensitivity analysis, the SMD values were not substantially influenced by sequentially removing individual studies. There was no publication bias. In meta‐regression, the effect size was not associated with other study and patient characteristics, including sex, Disease Activity Score‐28, C‐reactive protein and erythrocyte sedimentation rate. Conclusions: NLR and PLR can significantly discriminate between RA patients with and without active disease. Further studies are required to determine their diagnostic performance, singly or in combination with other parameters, in routine practice. Abstract : NLR and PLR in RA patients in remission and with active disease.